FREQUENCY AND PREVALANCE OF ANOMALIES AND DEFORMATIONS OF DENTOMAXILLARY (DENTOGNATHIC) APPARATUS IN THE TRANSITIONAL PERIOD OF BITE - P.S. Flis; V.V. Filonenko; N.M. Doroshenko (Ukrainian Medical Stomatological Academy, 2016)
Relevance of research. Studies of frequency and prevalence of teeth anomalies and deformities are required to develop the organizational principles of prevention and provide timely specialized medical care. Violations not only harm the child's health, but also adversely affect their adaptation to the social environment. The aim of the research. To set frequency of dental apparatus abnormalities and deformities in children with transitional period of bite at school of northern region of Ukraine. Materials and methods. To achieve this purpose the clinical and statistical methods are used. Clinical examination of patients was performed by the standard scheme. During examination of the oral cavity was evaluated placing of lips and tongue frenulums, palate configuration, teeth, dentition, alveolar process and bite. Also shape and position of individual teeth, the amount of space for them in the dental arch were being checked. Results and discussion. Among 724 children, dental apparatus anomalies and deformations were installed in 641 cases, which is 88.54%. Pathology was not found among 83 children (11.46%). According to our data, dental apparatus anomalies and deformations are often complex. Among children, who had teeth and jaws abnormalities (641), in 624 (97.35%) a multiple pathology was established, only in 17 (2.65%) - single pathology. We found that distal occlusion - the most common bite pathology, which was found in 376 (51.93%) children of the total number of surveyed children (724), mesial - 53 (7.32%), open - 22 (3.04%), deep - 282 (38.95%), cross - 32 (4.42%). Anomalies of the teeth were set in 541 people (74.72%). Other pathologies were found in 12 people (1.66%). Conclusion. Due to results of the examination of 6 - 12 years old children, the prevalence of dental abnor- malities and deformities of dental apparatus reaches 88.6%. The high frequency and prevalence of teeth anomalies and deformities largely depend on the level of treatment and preventive care, which needs the development of new, sustainable and available methods of treatment and prevention.